Homeobox transcription factor Meis1 is crucial to Sertoli cell mediated regulation of male fertility. (23rd November 2020) - Sarkar, Rajesh K.; Sen Sharma, Souvik; Mandal, Kamal; Wadhwa, Neerja; Kunj, Neetu; Gupta, Alka; Pal, Rahul; Rai, Umesh; Majumdar, Subeer S.
Abstract: Background: Infertility has become a global phenomenon and constantly declining sperm count in males in modern world pose a major threat to procreation of humans. Male fertility is critically dependent on proper functioning of testicular Sertoli cells. Defective Sertoli cell proliferation and/or impaired functional maturation may be one of the underlying causes of idiopathic male infertility. Using high‐throughput "omics" approach, we found binding sites for homeobox transcription factor MEIS1 on the promoters of several genes up‐regulated in pubertal (mature) Sertoli cells, indicating that MEIS1 may be crucial for Sertoli cell‐mediated regulation of spermatogenesis at and after puberty. Objective: To decipher the role of transcription factor MEIS1 in Sertoli cell maturation and spermatogenesis. Materials and methods: Sc‐specific Meis1 knockdown (KD) transgenic mice were generated using pronuclear microinjection. Morphometric and histological analysis of the testes from transgenic mice was performed to identify defects in spermatogenesis. Epididymal sperm count and litter size were analyzed to determine the effect of Meis1 knockdown on fertility. Results: Sertoli cell (Sc)‐specific Meis1 KD led to massive germ cell loss due to apoptosis and impaired spermatogenesis. Unlike normal pubertal Sc, the levels of SOX9 in pubertal Sc of Meis1 KD were significantly high, like immature Sc. A significant reduction in epididymal sperm count was observed in these mice. The mice were found to be infertile or sub‐fertile (with reduced litter size), depending on the extent of Meis1 inhibition. Discussion: The results of this study demonstrated for the first time, a role of Meis1 in Sc maturation and normal spermatogenic progression. Inhibition of Meis1 in Sc was associated with deregulated spermatogenesis and a consequent decline in fertility of the transgenic mice. Conclusions: Our results provided substantial evidence that suboptimal Meis1 expression in Sc may be one of the underlying causes of idiopathic infertility.